PLANNING OF DRINKING WATER SUPPLY SYSTEM DEVELOPMENT BASED ON ANALYSIS OF COMMUNITY PURCHASING POWER OF CLEAN WATER TARRIF (PDAM) IN BANDUNG USING CONTINGENT VALUATION METHOD (CVM) (Regional Studies in Seven Districts in the City of Bandung) - Akmaludin, Muhamad
Water is an important factor in human life. Water is used for various purposes including drinking, domestic use, and all human activities. The research objective was to analyze the economic value of clean water services and the factors that influence the value of willingness to pay (WTP) for PDAM of Bandung City services payment. The method used in this study was the Contingent Valuation Method (CVM). CVM is a survey technique that asks residents about the value or price of the paid commodity they receive which does not have market value as a utility. The factors that influenced the willingness to pay for utility services in this study are the mean household income, the number of water users, and the amount of water demand. The WTP value obtained from this study is the value that will be given by respondents for clean water services in PDAM Kota Bandung per cubic meter per household. The average WTP value of respondents in first scenario is Rp5,992/m3/month, while the average WTP value of the second scenario is Rp7,534/m3/month. While the average ATP value of respondents is Rp3,752, which is smaller than the value of WTP, it can be said that the willingness to pay the community to pay for PDAM services is greater than its ability, so that PDAM of Bandung City can improve services by developing a drinking water supply system, there are two alternative systems, namely alternative system 1 with raw water sources originated from Ciwidey watershed with capacity of 1,800 lps while alternative systems 2 with raw water sources of Cikalong intakes have a capacity of 1,400 lps. The chosen alternative system is an alternative system for developing drinking water supply using raw water sources from the Cikalong Intake and Santosa Reservoir with a capacity of 1,400 lps,, the investment value needed for this system is Rp949,520310,260 and this alternative systems are feasible.